‘Patria ruens.’ Ruining and Overcoming Evil – the Example of Selected Poems by Claudian - Petry, Martyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The paper focuses on longer poems by the court poet Claudian that depict a State ruined by evil forces or the state of harmony. This poet from late Antiquity uses a vocabulary related to death and destruction. Evil, above all barbarians and political opponents, is also presented appropriately by the poet. Their characters function in the poems as disaster, ruin and ignominy. To depict these evil forces, their repeatability and how they are overcome on different levels, the poet uses the motive of the upward and downward movement, describing a dead character‘s way up to heaven and down to the underworld. Destruction rises from this movement of evil to the upper world, while the movement down to the underworld carries liberation and peace. Nevertheless, the poet implies, that the state of harmony is never definitive. Destruction and ruin repeat and recur in different forms in the poems, from the mythological past up to the present. In this sense, the characters in these poems function within a time loop and the story world presents the poet’s view on history and how it works on the divine and human level.